The determinants of bargaining power in an empirical model of transfers between adult children, parents, and in-laws for South Korea - Ham, John C.; Song, Heonjae (Journal of development economics, 2014)
We derive a bargaining model of transfers between adult children and their parents, and then estimate the model using data from South Korea. Our analysis extends the literature on family bargaining by i) arguing that transfers from the couple represent semiprivate consumption (e.g. it is plausible that the wife cares more about her parents than about the husband's parents, and vice-versa) and ii) using results from laboratory experiments to help identify the model. We find that women have slightly more bargaining power than men in the couple's decision making. We also find that when an adult child receives an extra dollar of income, she transfers half of it to her parents; this result is consistent with previous work. Finally, we reject the null hypothesis that bargaining power within the family depends only on the potential wage of each spouse. •We estimate a model of transfers between Korean married children and parents.•We use results from laboratory experiments to help identify the model.•We find that women have slightly more bargaining power than men.•Each partner's bargaining power is increasing in their education.•Children transfer 50% of any increase in income to their parents.